2018
DOI: 10.1371/journal.pone.0207182
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and suicidal behaviours in adolescent non-daily smokers compared to daily smokers and never-smokers in Korea: National cross-sectional study

Abstract: IntroductionWe aimed to investigate the association of non-daily smoking with depressive symptoms and suicidal behaviours among adolescents by analysing data from the 2016 Korean Youth Risk Behavior Web-based Survey (KYRBWS), a national school-based survey.MethodsWe analysed data from a nationally representative sample of Korean adolescents aged 12–18 years (n = 65,528). We investigated the risks of depressive symptoms, suicide ideation, plan and attempt in adolescent non-daily smokers using multiple logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
1
13
3
Order By: Relevance
“…These findings differ to what has been found in most studies with cross-sectional analyses in which different smoking behaviors have been related to depressive symptoms (Lee et al, 2018;Moon et al, 2010;Tjora et al, 2014). For example, Tjora et al, (2014) found that daily smoking was associated with depressive symptoms in cross-sectional analyses in almost all waves of data from the study, starting during early adolescence when participants were 13 years old to adulthood when they were 30 years old.…”
Section: Relationship Between Cigarette Smoking and Depressive Symptomscontrasting
confidence: 96%
See 2 more Smart Citations
“…These findings differ to what has been found in most studies with cross-sectional analyses in which different smoking behaviors have been related to depressive symptoms (Lee et al, 2018;Moon et al, 2010;Tjora et al, 2014). For example, Tjora et al, (2014) found that daily smoking was associated with depressive symptoms in cross-sectional analyses in almost all waves of data from the study, starting during early adolescence when participants were 13 years old to adulthood when they were 30 years old.…”
Section: Relationship Between Cigarette Smoking and Depressive Symptomscontrasting
confidence: 96%
“…Not only has daily smoking been associated with depressive symptoms, but also occasional smoking. In a more recent study conducted in Korea, Lee et al (2018) showed that adolescents ages 12 to 18 with depressive symptoms were more likely to occasionally smoke in comparison to those who did not show elevated symptoms of depression.…”
Section: Relationship Between Cigarette Smoking and Depressive Symptomsmentioning
confidence: 97%
See 1 more Smart Citation
“…and recorded on a five-point Likert scale (low = 1, mid-low = 2, mid = 3, mid-high = 4, high = 5) [39]. The scale was converted into a three-level variable (low/mid-low = 1, mid = 2, mid-high, high = 3) [40]. High scores indicate high academic achievement.…”
Section: Academic Achievementmentioning
confidence: 99%
“…A recent systematic review found that current cigarette smokers (i.e., smoked at least 100 cigarettes and smoked in the past 30 days) were nearly twice as likely to report suicidal ideation, suicide planning, and suicide attempts compared to non-smokers [ 6 ]. Moreover, cigarette smoking is associated with depression [ 7 ], a leading predictor of suicidal behavior [ 8 ].…”
Section: Introductionmentioning
confidence: 99%